Penerapan Kunjungan Gembala terhadap Pertumbuhan Rohani Jemaat Berdasarkan Matius 25:36 - Brightly Nehemia Junior Siringoringo; Freddy Manurung (Journal on Education, 2024)
This research aims to explore the role and impact of pastor visitation on the spiritual growth of the congregation, with reference to the verse Matthew 25:36. The research method used is a quantitative approach through the use of a structured random sample with online questionnaire distribution (Google Form) to 54 respondents. Data analysis was conducted using simple linear analysis method, t test (partial), F test (ANOVA), and descriptive statistical analysis. The results showed a simultaneous positive and significant influence between pastoral visitation and congregational spiritual growth, with an ANOVA calculated value of 35.987 ≥ the F table value of 3.99 and a significance level of 0.000. Partial tests revealed that pastoral visitation partially has a positive and significant influence on the spiritual growth of church members based on Matthew 25:36, with a t-test value of 5.999 ≥ 1.99834 and a significance level of 0.000. This finding contributes to the understanding of the role of pastoral visitation in the context of congregational spiritual growth, as well as its implications for the development of pastoral practices in the church environment.